Integrated Geophysical Investigation of Lead-Zinc Mineralization in Awgu- Ndeabor Southeastern Nigeria Using Magnetic and Electrical Resistivity Methods - Ekechi , Mmaduabuchi; Ezeh, Chukwudi; Okonkwo, Austin (European Journal of Applied Sciences, 2025)
An integrated geophysical investigation combining magnetic survey, electrical resistivity tomography (ERT), and core drilling was conducted to delineate lead-zinc mineralization in the Ndeabor area of southeastern Nigeria. The magnetic survey was performed using the GSM-19 Overhauser magnetometer, targeting three blocks with profiles oriented east–west. Analytical signal, first vertical derivative, and residual magnetic intensity maps were generated to enhance anomaly detection. Two-dimensional ERT was carried out along selected traverses to characterize subsurface resistivity contrasts. Core drilling was employed at locations with identified surface mineralization, with eight boreholes drilled to evaluate vertical continuity. Magnetic field intensity values ranged from 33,350 nT to over 33,600 nT, with high anomalies indicating possible doleritic intrusions and fault-controlled structures. Analytical signal amplitudes reached 0.0035 nT/m, and first vertical derivative highs were up to ±0.0026 nT/m². Residual magnetic intensity (RMI) values ranged from -69.8 nT to +89.2 nT. The ERT survey revealed resistivity variations between <10 Ωm and >1500 Ωm, consistent with lithological contacts and potential sulfide-bearing zones. Core drilling intercepted lead-zinc-bearing pyroclastic rocks in five of eight boreholes, with thicknesses ranging from 3 to 8 meters (average 5.5 m), confirming mineral continuity beneath surface exposures. This integrated approach significantly enhanced subsurface characterization, reduced interpretational ambiguity, and provides a reliable framework for future mineral exploration in the Lower Benue Trough.